PERAN PEMAHAMAN TEKNOLOGI SEBAGAI PEMEDIASI DALAM KEPUTUSAN MEMBAYAR ZAKAT, INFAK, SEDEKAH MELALUI APLIKASI MOBILE BANKING : (STUDI EMPIRIS PADA MASYARAKAT DI WILAYAH JABODETABEK) - Wahid, Abdurrachman; Riskayanto, Riskayanto (Universitas Dharmawangsa, 2025)
This study aims to examine the role of technological understanding as a mediator in the decision-making process of the Jabodetabek community to pay Zakat, Infak, and Sadaqah (ZIS) through mobile banking applications. The background of this research is based on the rapid development of digital technology and the increasing use of mobile banking in Indonesia, which has the potential to encourage the digital distribution of ZIS. This study employs a quantitative method with an associative approach, utilizing questionnaires to collect data from 250 mobile banking users in Jabodetabek who have conducted ZIS transactions. Data analysis utilizes Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The findings reveal that perceptions of ease of use, trust, and benefits simultaneously and significantly influence technological understanding and the decision to pay ZIS. Partially, trust significantly and positively impacts technological understanding and the decision to pay ZIS, while perceptions of ease of use and benefits only partially influence the decision to pay ZIS. Technological understanding also significantly affects the decision to pay ZIS. The variable of trust has the most dominant influence on technological understanding, while the variable of perceived benefits has the most dominant influence on the decision to pay ZIS.